Managing risks in work-integrated learning programmes: a cross-institutional collaboration. Issue 2 (11th December 2019) - Cameron, Craig; Ashwell, Janine; Connor, Melissa; Duncan, Mary; Mackay, Will; Naqvi, Jeff
Abstract : Purpose: Work-integrated learning (WIL) poses legal, reputation, operational, strategic and financial risks for higher education providers (HEPs). The purpose of this paper is to explore how HEPs can manage five significant WIL risks involving intellectual property, student disability and medical conditions, the host organisation and the legal literacy of WIL practitioners. Design/methodology/approach: This paper is a cross-institutional collaboration of WIL practitioners who explored risk management in WIL programmes. The case study is presented as a cross-case analysis to assist WIL stakeholders with evaluating their risk management frameworks. A description about the significance of the risk (in terms of causes and consequences), as well as practices to manage the risk, is presented under each of the five WIL risks. Findings: WIL practitioners described a series of risk management practices in response to five significant risks in WIL programmes. Four themes underpinning these risk management practices – balance, collaboration, relationship management and resources – are conceptualised as characteristics that can serve as guiding principles for WIL stakeholders in risk management. Practical implications: The findings can be applied by WIL stakeholders to evaluate and improve existing risk management frameworks, and to improve their legal literacy in relation to WIL. The study also demonstrates the capacity for collaborative research to address practice issues in WIL. Originality/value: This is the first known study which employs a cross-institutional collaboration of WIL practitioners to contribute towards the body of knowledge examining risk management in WIL programmes.